1998
DOI: 10.1139/cjpp-76-1-16
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-activating peptides distinguish thrombin receptor (PAR-1) and protease activated receptor 2 (PAR-2) mediated hemodynamic responses in vivo

Abstract: Vascular expression and cellular functions of the thrombin receptor (PAR-1) and protease activated receptor 2 (PAR-2) suggest similar but distinct vascular regulatory roles. The vascular actions of PAR-1 and PAR-2 in vivo were differentiated by monitoring mean arterial pressure (MAP) and heart rate (HR) of anesthetized mice in response to intravenous SFLLRN (0.1, 0.3, and 1 mumol/kg) and SLIGRL (0.1, 0.3, and 1 mumol/kg), the respective receptor-activating sequences for PAR-1 and PAR-2, and TFLLRNPNDK (0.3, 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 41 publications
4
22
0
Order By: Relevance
“…Consistently with previously published data, PAR-1 deficiency had no significant effect on the baseline diastolic and systolic BP (Supplement 1) [24, 25]. Interestingly, infusion of Ang II at the concentration of 600ng/kg/min caused only modest but not statistically significant increase of BP in both WT and PAR-1 −/− mice measured at day 7 and 28 after initiation of infusion (Supplement 1).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Consistently with previously published data, PAR-1 deficiency had no significant effect on the baseline diastolic and systolic BP (Supplement 1) [24, 25]. Interestingly, infusion of Ang II at the concentration of 600ng/kg/min caused only modest but not statistically significant increase of BP in both WT and PAR-1 −/− mice measured at day 7 and 28 after initiation of infusion (Supplement 1).…”
Section: Resultssupporting
confidence: 90%
“…These studies suggest that PAR-1-dependent vasoregulation may be cell/tissue specific. In mice, activation of PAR-1 with agonist peptide results in a biphasic BP response in which there is a rapid and transient hypotension followed by sustained HTN, presumably via activation of PAR-1 on smooth muscle cells [24]. Unstressed PAR-1 −/− mice exhibit no obvious abnormalities in baseline BP compared to PAR-1 +/+ mice [24, 25].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of PAR activators on cardiovascular responses have been investigated in intact animals. In mice, intravenous injection of PAR 1 -selective AP causes a rapid and sustained hypotension, which is not NO mediated (47). Similarly, in rats and mice, PAR 2 activators cause hypotension by NO-dependent and -independent mechanisms, which can be followed by a reflex hypertension (52).…”
Section: Par Signaling To the Vesselsmentioning
confidence: 98%
“…However, the effect of PAR-2 on peripheral sympathetic activity, which regulates peripheral vascular resistance, is not fully understood. According to previous reports, hypotension induced by PAR-2 activation is maintained for around 2–3 min, and the ganglion-blocking agent chlorisondamine significantly increases the duration of hypotension induced by PAR-2 activation, suggesting that PAR-2-induced hypotension may be maintained by modulating peripheral sympathetic tone ( Cheung et al, 1998 ; Cicala et al, 2001 ; Emilsson et al, 1999 ). However, a detailed mechanism for PAR-2 induced suppression of peripheral sympathetic outflow has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 63%
“…Recently, it has been reported that PAR-2 is highly expressed in endothelial cells and vascular smooth muscle, suggesting a crucial role in regulating vascular tone ( al-Ani et al, 1995 ; Hollenberg et al, 1996 ; Magazine et al, 1996 ; Saifeddine et al, 1996 ). In fact, PAR-2 activation by receptor-activating peptides decreases blood pressure in anesthetized rats or mice in vivo ( Cheung et al, 1998 ; Cicala et al, 1999 ; 2001 ; Damiano et al, 1999 ; Emilsson et al, 1997 ; Kawabata et al, 2003 ). This hypotension is only partially inhibited by the nitric oxide synthase inhibitor, L-NAME, suggesting that a nitric oxide (NO)-independent mechanism as well as a NO-dependent mechanism are involved in hypotension induced by PAR-2 activation ( Cicala et al, 2001 ; Emilsson et al, 1997 ).…”
Section: Introductionmentioning
confidence: 99%